Instrumento portátil para aquisição, digitalização e processamento de imagens a ser aplicado na avaliação do sistema de equilíbrio humano - Prestes, Lucas Plautz (2013)
This thesis describes a new human balance analysis instrument for studies on the physiology of the vestibular system, support for diagnostics, patient evolution in treatment and in the adaptation process of physiotherapy and vestibular disorders. Various techniques used to evaluate balance are subjective, imprecise and invasive. In the present work, a device has been developed to objectively measure human balance in a non-invasive manner with adequate precision. The objectives of this thesis were: (1) to improve image processing techniques, (2) to reduce equipment production costs, (3) to facilitate portability, (4) to develop a robust, scalable and easily maintained software architecture. The vestibular system is located in the inner ear, and it is responsible for maintaining balance. The vestibular system is composed mainly of a network of tubes called semicircular canals, which are stimulated by selective head movements. Through vestibular-motor reflexes, eye movements are induced which correspond to head movement. The images of the eye movements are acquired by video cameras, under infrared illumination. The cameras are mounted to glasses isolated from external light developed for the purposes of this research. The camera images are digitalized by an external capture card and processed in real time by an algorithm developed to, frame by frame, locate the center of the pupil. The location of the center of the pupil in response to the vestibulo-ocular stimulus is plotted into a graph, to then be interpreted by a medical specialist. The tests carried out prove the efficiency and robustness of the algorithm in calculating the center of the pupil with a broad range of variations. The tests include a number of variations of the pupil and elliptical eye distortions with additional reflections occasioned by sources of illumination. All tests had a negligible error, thus proving their efficiency and meeting their objective.